Authenticated encryption of pmu data - Gaona García, Elvis Eduardo; Rojas Martínez, Sergio Leonardo; Trujillo Rodríguez, Cesar Leonardo; Mojica Nava, Eduardo Alirio (Tecnura, 2014)
This paper presents the implementation of anencryption board in order to provide confidentiality, authenticity and integrity of data collected at any point in a power grid, as a potential solution to the Smart Grid cyber security issues. This board consists of a Freescale microcontroller which enables the connection between a PMU (Phasor Measurement Unit) and a ZigBee transmitter. Encryption is done using the SHA256, HMAC-SHA256, KDF-SHA256 and AES256-CBC algorithms. This architecture makes reading and transmission of voltage and currentphasors, energy consumption, frequency, power, power factor and power outages measurements and sendsthis information in real time to a data concentrator where display and subsequent storage are possible.